2018
DOI: 10.1089/neu.2017.5188
|View full text |Cite
|
Sign up to set email alerts
|

Transient Hypertension after Spinal Cord Injury Leads to Cerebrovascular Endothelial Dysfunction and Fibrosis

Abstract: We aimed to create a clinically relevant pre-clinical model of transient hypertension, and then evaluate the pathophysiological cerebrovascular processes resulting from this novel stimulus, which has recently been epidemiologically linked to cerebrovascular disease. We first developed a clinically relevant model of transient hypertension, secondary to induced autonomic dysreflexia after spinal cord injury and demonstrated that in both patients and rats, this stimulus leads to drastic acute cerebral hyperperfus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 39 publications
4
26
1
Order By: Relevance
“…Further research is required to elucidate whether a threshold exists above which CRF will be associated with an attenuated dCA. In addition, Phillips et al () have recently reported that 4 weeks of repeated transient hypertension induced by colorectal distension in rats after spinal cord injury lead to impairments of the brain vasculature such as cerebrovascular endothelial dysfunction and profibrotic cerebrovascular stiffness (Phillips et al, ). Unfortunately, we did not monitor BP changes during our HIIT sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to elucidate whether a threshold exists above which CRF will be associated with an attenuated dCA. In addition, Phillips et al () have recently reported that 4 weeks of repeated transient hypertension induced by colorectal distension in rats after spinal cord injury lead to impairments of the brain vasculature such as cerebrovascular endothelial dysfunction and profibrotic cerebrovascular stiffness (Phillips et al, ). Unfortunately, we did not monitor BP changes during our HIIT sessions.…”
Section: Discussionmentioning
confidence: 99%
“…Regular exposure to such extreme intermittent hypertension, and associated rapid changes in cerebral perfusion, may induce structural modifications in the cerebrovasculature. For example, pre‐clinical animal models utilizing 4 weeks of repeated transient hypertension induced cerebrovascular endothelial dysfunction and profibrotic mediated cerebrovascular stiffness (Phillips et al., ). We speculate that this modification may underlie the tendency for a reduced phase in the resistance‐trained group.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported as many as 41 autonomic dysreflexia events occur each day (mean = 11/day) in individuals with high-level SCI [28]. Recent evidence in pre-clinical models demonstrates diverse cerebrovascular impairments with chronic exposure to repetitive episodes of transient hypertension following SCI [29]. Chronic hypertension in non-disabled individuals is strongly and consistently associated with cognitive decline [30].…”
Section: Introductionmentioning
confidence: 91%